Orthodontic Treatment Need and Complexity among 13-15 Year-Old Schoolchildren in Kerman, Iran - Mahsa Kalantari; Hosnieh Ziaalddini; Mohammadreza Jaffari; Parisa Kalantari (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Effective and informed planning for orthodontic services in any population requires assessment of the orthodontic treatment need and complexity. Purpose: The present cross-sectional study was conducted to assess these parameters using index of complexity, outcome, and need (ICON) in an Iranian schoolchildren population. Materials and Method: In total, 600 randomly selected individuals (300 girls, 300 boys; aged 13-15 years) participated in this study. The treatment need (ICON score>43) and the grades of complexity were compared between two genders and in different age groups. Descriptive statistics and Chi-square test were applied for data analysis considering p< 0.05. Results: Out of 45% of the population found in need for orthodontic treatment, there was no significant difference between the two genders, but the 15-year-old individuals needed treatment significantly more than the individuals with 13 and 14 years of age. The mean ICON score was 44.3±20.28, which showed no significant difference between the two genders. The majority of the cases (34%) were categorized in the easy compartment in terms of complexity and 18% had difficult or very difficult grades of complexity. The genders and age groups exhibited no significant difference in terms of the complexity grade. Conclusion: Although half of the studied cases needed treatment, nearly one-fifth had difficult or very difficult complexity grade, which indicates the need for specialist care.